“FAOLIYAT, EMOTSIYA VA MOTIVATSIYA” (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article analyzes the psychological role of emotions and motivation in the process of individual activity, their mechanisms of interdependence, and their impact on human behavior and cognitive processes from a theoretical and practical perspective. Activity is considered as the main form of action in the social life of an individual, and emotion is studied as a mental state that organizes activity and a recording tool. Motivation is explained as a source of internal energy for conscious goal-directed action. The article analyzes the scientific views of psychologists such as Vygotsky, Leontiev, Rubinstein, Maslow, McClelland, Simonov, and scientifically explains the formation of the motivational system of activity, mechanisms of emotional regulation, and the processes of development of volitional control by a person. The article also provides practical recommendations on factors for increasing motivation for study, forming emotional stability, and effective activity in students.